2019
DOI: 10.1002/ajmg.a.61062
|View full text |Cite
|
Sign up to set email alerts
|

Hyperinsulinemic hypoglycemia in seven patients with de novo NSD1 mutations

Abstract: Sotos syndrome is an overgrowth syndrome characterized by distinctive facial features and intellectual disability caused by haploinsufficiency of the NSD1 gene. Genotype-phenotype correlations have been observed, with major anomalies seen more frequently in patients with 5q35 deletions than those with point mutations in NSD1. Though endocrine features have rarely been described, transient hyperinsulinemic hypoglycemia (HI) of the neonatal period has been reported as an uncommon presentation of Sotos syndrome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
1
10
0
1
Order By: Relevance
“…The precise mechanism of dysregulated insulin secretion in Sotos syndrome is unknown. Notably, the gene product of NSD1 is a histone methyltransferase that is known to be involved in the regulation of chromatin and gene expression, and circumstantial evidence exists that NSD1 may thereby also regulate islet cell insulin expression ( 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…The precise mechanism of dysregulated insulin secretion in Sotos syndrome is unknown. Notably, the gene product of NSD1 is a histone methyltransferase that is known to be involved in the regulation of chromatin and gene expression, and circumstantial evidence exists that NSD1 may thereby also regulate islet cell insulin expression ( 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, one of the hypotheses proposed is that the 5q35 region may also include additional genes that could be implicated in HH 21‐23 . It has been reported that major anomalies are associated more frequently with 5q35 deletions compared to point mutations in NSD1 24 . NSD1 gene encodes a histone methyltransferase that is involved in the opening and closing of chromatin.…”
Section: Discussionmentioning
confidence: 99%
“…NSD1 gene encodes a histone methyltransferase that is involved in the opening and closing of chromatin. Disrupted interaction between NSD1 and cofactors or histones could lead to abnormal expression of insulin, or perhaps the association of NSD1 and certain β‐cell transcription factors could suppress the expression of the insulin gene 24,25 …”
Section: Discussionmentioning
confidence: 99%
“…Ayrıca, prenatal başlangıçlı teratomların postnatal başlangıçlı teratomlara göre daha kötü prognozlu olduğu (7,8), literatürde; Sotos sendromu ve sakrokoksigeal teratomun birlikte görüldüğü 2000 yılında iki (13), 2019 yılında iki vaka olmak üzere, toplam 4 vaka bildirilmiştir. Bu tür tümörlerin rastlantısal olabileceği gibi, aşırı büyümenin tümör gelişimini uyarıcı etkisine bağlı olarak da gelişebileceği belirtilmektedir (14). SONUÇ Sonuç olarak; Sotos sendromu tanısı konulan olgumuzda NSD1 geninde tespit edilen heterozigot değişim de novo olup patojenik varyant olarak kabul edildi.…”
Section: Introductionunclassified